Manajemen Dakwah MUI dalam Mewujudkan Moderasi Beragama di Kabupaten Deli Serdang - Kurniawan, Rhohis; Fachran Haikal, Muhammad (Islamic Management and Empowerment Journal, 2024)
This research aims to find out how the MUI’s missionary management is in realizing religious moderation in Deli Serdang Regency. This research method uses qualitative with a qualitative approach. Data collection was carried out using observation, interviews and documentation techniques. The results of this research are that MUI da’wah management applies planning, organizing, mobilizing and evaluating da’wah. So that the impact felt by the community can achieve a religious harmony index of up to 70%. This is a pretty good predicate for increasing awareness of living in tolerance.